IMPORTANCE OF DEVELOPING ORAL COMMUNICATION SKILLS FOR LEARNERS (Western European Journal of Linguistics and Education, 2024)
Oral communication skills are fundamental for learners as they significantly enhance academic and professional performance. Developing these skills equips students with the ability to express ideas effectively, engage in collaborative environments, and improve critical thinking and active listening. This paper highlights the importance of fostering oral communication skills in educational settings, emphasizing their role in boosting confidence, enhancing social interactions, and preparing students for real-world challenges. Various methods and strategies for improving these skills, such as active participation, group discussions, and presentation practices, are explored to illustrate their positive impact on learners' overall development.